MR and CT in cytoplasmically inherited striatal degeneration. - Seidenwurm, D; Novotny, E; Marshall, W; Enzmann, D (American Journal of Neuroradiology, 1986)
A rare, cytoplasmically inherited striatal degeneration associated with Leber's optic atrophy exhibited selective symmetric low-density lesions in the putamen on the CT scan in five patients. The CT findings, however, were asymmetric (one patient) and subtle in the early phases of the disease. Occasionally, caudate lesions were demonstrable. On MR imaging, the lesions had high signal intensity on T2-weighted images and low signal intensity on T1-weighted images. This group of patients was distinguished from patients with other causes of striatal degeneration by a lack of hemispheric, brainstem, or cerebellar atrophy.